Poly(2,5-Benzimidazole) as a membrane material for solvent dehydration: effect of bound methanesulfonic acid - Alladi, Lavanya; Lele, Ashish K.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2025)
Towards addressing issues of solvent stability of polymeric membrane materials for pervaporation (PV), this work investigates thermochemically robust poly(2,5-benzimidazole) (ABPBI) bound with methane sulfonic acid (MSA) for solvent dehydration, for the first time to our knowledge. Phase inversion membranes with and without bound-MSA were prepared, thermally treated at different temperatures up to 350 degrees C, and analyzed for physical and pervaporation properties. The physical characterizations (FTIR, WAXD, TGA, XPS, SEM, and EDX) and sorption analysis were performed using flat sheet membranes, whereas hollow fiber membranes were used for the pervaporation analysis with chosen solvents (alcohols and two polar aprotic solvents). Physical characterizations established the presence of MSA and the nonporous, dense nature of membranes, irrespective of their treatment temperatures. The sorption of pure solvents in the membrane is primarily affected by thermal treatment of the membranes. The pervaporation analysis was performed using different solvent: Water feed compositions. Using 85:15 as the feed, the average separation factors for dehydration of isopropanol, acetonitrile, and N,N-dimethylformamide (DMF) were 393, 213, and 185, respectively, with an appreciable ``pervaporation separation index.'' The long-term membrane performance till 360 h was analyzed to shed light on practical applicability.
Keywords: membranes; separation techniques; synthesis and processing techniques